Analysis of The Effect of Electronic Customer Relationship Management and Perceived Value on E-Customer Loyalty Through E-Customer Satisfaction on XYZ.Com (Bina Nusantara University, 2022)
Electronic Customer Relationship Management is an integrated CRM function with the use of an online environment to identify, attract and retain an organization’s customers. E-CRM has an important role in addressing the challenges that exist in the e-commerce industry and certainly affect the success of e-commerce. In an online business, perceived value is something that must be maintained, that it can become a company's advantage in competing. The purpose of this research is to identify the effect of Electronic Customer Relationship Management (E-CRM) and Perceived Value in increasing customer satisfaction and loyalty. This study used the method SEM-PLS with respondents as mush as 111 respondents. The results are significant againts Electronic Customer Relationship and Perceived Value on E-Customer Satisfaction and E-Customer Loyalty in JABODETABEK customer of XYZ.com.